Mechanisms underlying lack of functional compensation by insect grazers after tadpole declines in a Neotropical stream - Thomas R. Barnum; John Timothy Wootton; Rebecca J. Bixby; John M. Drake; David Murray‐Stoker; Checo Colón‐Gaud; Amanda T. Rugenski; Therese C. Frauendorf; Scott Connelly; Susan S. Kilham; Matt R. Whiles; Karen R. Lips; et al. (Limnology and Oceanography, 2022)
Resilience of ecosystems to the sudden decline of large‐bodied species is dependent on characteristics of surviving guild members. However, that response may also be mediated by local habitat conditions. Here, we examine the mechanisms behind the observed lack of functional compensation in the algal‐grazing guild by insect grazers following the decline of tadpole grazers in a forested Panamanian stream. We examined: (1) shifts to the individual size distribution of insect grazers between pre‐ and post‐tadpole declines in pool and riffle habitats; (2) tadpole and insect preferences for small‐, medium‐, and large‐sized diatoms; and (3) a causal explanation for why insects did not functionally compensate for tadpole declines. The size distribution of insect grazers following tadpole declines differed between habitats, becoming uniform in pools and more right skewed toward a smaller size class in riffles. In both habitats, tadpoles selectively consumed medium‐sized diatoms but avoided the largest‐sized diatoms. In contrast, grazing insects selectively consumed small‐sized diatoms, but switched to medium‐sized diatoms after tadpole declines. Tadpole declines led to the loss of the strongest interactions between consumers and diatoms. Smaller‐bodied grazing insects could not duplicate these interactions, even with a shift in resource use, providing an explanation for the lack of functional compensation. Furthermore, tadpole declines led to different community structures in each habitat indicating that local habitat conditions mediated the response of surviving guild members. This suggests that the sudden decline of a large‐bodied species does not lead to a singular outcome for the surviving community.